Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3174/ajnr.a4201
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Agreement Regarding the Role of Flow Diversion in the Management of Difficult Aneurysms

Abstract: BACKGROUND AND PURPOSE:The role of flow diversion in the management of aneurysms remains unknown. We sought to evaluate the community agreement regarding indications for flow diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 28 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…The use of FDS made coiling the BBA easier and safer 11 16. Interestingly, in a set of difficult aneurysms, the greatest agreement was found for BBA where FDS was considered the only option (5 of 22 responders) 38. Its increasing popularity together with encouraging personal experiences and satisfactory patient outcomes has supported the concept of flow diversion also in BBAs.…”
Section: Discussionmentioning
confidence: 97%
“…The use of FDS made coiling the BBA easier and safer 11 16. Interestingly, in a set of difficult aneurysms, the greatest agreement was found for BBA where FDS was considered the only option (5 of 22 responders) 38. Its increasing popularity together with encouraging personal experiences and satisfactory patient outcomes has supported the concept of flow diversion also in BBAs.…”
Section: Discussionmentioning
confidence: 97%
“…A recent survey has shown that clinicians favor flow diversion of aneurysms with lateral wall morphologies rather than other types of lesions, including bifurcation aneurysms 2. However, some bifurcation aneurysms have been treated successfully by flow diversion 2–8…”
Section: Introductionmentioning
confidence: 99%
“…We have found that for simple questions with a binary outcome, as a rule of thumb a minimal number of ten raters reviewing 30-50 patients is necessary for the study to be informative. [6][7][8]20] There are many statistical approaches to measure reliability and agreement, depending on the type of data (categorical, ordinal, continuous), the sampling method and on the treatment of errors. [1] Reliability in treatment recommendations (categories) is most frequently analyzed using kappa-like statistics.…”
Section: Statistical Power and Analysesmentioning
confidence: 99%